Giant Muscle Invasive Dermatofibroma Clinically Mimicking a Malignant Tumor. (28th March 2019) - Kinoshita, Hideyuki; Ishii, Takeshi; Kamoda, Hiroto; Tsukanishi, Toshinori; Orita, Sumihisa; Inage, Kazuhide; Ohtori, Seiji; Yonemoto, Tsukasa
Abstract : Dermatofibromas are common benign fibrohistiocytic lesions, usually appearing as slow growing firm dermal nodules with a predilection for the extremities (mostly the lower legs). They are found mostly in middle-aged women and are usually smaller than 2 cm in diameter. Giant dermatofibromas exceeding 5 cm in diameter are rare. In recent years, reports have suggested a relationship between the primary size of dermatofibromas and rates of local recurrence and metastases after surgery. This relationship is however debated. The present report describes the case of a giant muscle invasive tumor in a 51-year-old female patient who presented with a large ulcerated mass in the right upper arm. The tumor appeared clinically malignant, measuring approximately 12 cm × 6 cm in size, with ulceration and invasion of surrounding muscle. Wide resection of the tumor was performed with myocutaneous flap-plasty. Histopathological examination showed evidence of a dermatofibroma. No recurrence, metastases, or other complications were noted at 5 years after surgery. The present case demonstrates that although dermatofibromas are essentially benign, they may present with atypical features including large size, ulceration, and muscle invasion, clinically mimicking malignant tumors.